Check for Plagiarism Using Text Mining - Umidakhon Zukharova (Zien Journals, 2023)
The internet provides answers to all queries in the modern world. Therefore, anybody may quickly copy and utilize material from the web at any time. Plagiarism is what is meant by this. It is currently expanding. Typically, when someone plagiarizes a piece of writing, they rephrase, duplicate, and omit sources. Plagiarism is difficult to identify since individuals often paraphrase texts rather than copying them verbatim. The Apache Lucene plagiarism detector has been utilized. The original document is first indexed, and the copied document is then compared to a collection of previously stored documents using cosine similarity.
Keywords: Indexing; Apache Lucene; Cosine similarity